Given that height, h(t) of a tennis ball is modeled by the equation h(t)=<span>-16t^2 + 45t + 7, the time taken for the ball to reach maximum height will found as follows:
at maximum height:
h'(t)=0
but from the equation:
h'(t)=-32t+45=0
solving for t we get
t=45/32
t=1.40625~1.4 seconds
Thus the time taken to reach maximum height is 1.4 seconds
</span>
Answer:
2 cases of soya bean milk will have the same volume as 1 case of fruit juice.
Step-by-step explanation:
Let the case of soya beans drink be x and let the case of fruit juice be y
We are told that the room can store either 10 cases of soya beans drink and 8 cases of fruit juice or 4 cases of soybeans drink and 11 cases of fruit juice.
This means that;
10x + 8y = 4x + 11y
Rearranging, we have;
10x - 4x = 11y - 8y
6x = 3y
Thus;
y = 6x/3
y = 2x
This means that 2 cases of soya bean milk will have the same volume as 1 case of fruit juice.
<u>Statement Reason </u>
AB║CD , AD║CB Given
m∠BAC = m∠ACD Alternate Interior Angles
m∠ACB = m∠CAD Alternate Interior Angles
AC = AC Reflexive Property of Equality
ΔABC ≅ΔCDA ASA ≅
Answer:
Step-by-step explanation:
if we're estimating ,we're going to round up to 8 since you can multiply that easier. 25 times 8 is 200 so estimation will be around 200
Answer:
B. (b+3c)+(b+3c)
C. 2(b)+2(3c)
Step-by-step explanation:
we have
![2(b+3c)](https://tex.z-dn.net/?f=2%28b%2B3c%29)
Distribute the number 2
![2(b+3c)=2b+2(3c)=2b+6c](https://tex.z-dn.net/?f=2%28b%2B3c%29%3D2b%2B2%283c%29%3D2b%2B6c)
Verify each case
case A) 3(b+2c)
distribute the number 3
![3(b+2c)=3b+3(2c)=3b+6c](https://tex.z-dn.net/?f=3%28b%2B2c%29%3D3b%2B3%282c%29%3D3b%2B6c)
![3b+6c \neq 2b+6c](https://tex.z-dn.net/?f=3b%2B6c%20%5Cneq%202b%2B6c)
therefore
Choice A is not equivalent to the given expression
case B) (b+3c)+(b+3c)
Combine like terms
![b+3c)+(b+3c)=(b+b)=(3c+3c)=2b+6c](https://tex.z-dn.net/?f=b%2B3c%29%2B%28b%2B3c%29%3D%28b%2Bb%29%3D%283c%2B3c%29%3D2b%2B6c)
![2b+6c= 2b+6c](https://tex.z-dn.net/?f=2b%2B6c%3D%202b%2B6c)
therefore
Choice B is equivalent to the given expression
case C) 2(b)+2(3c)
Multiply both terns by 2
![2(b)+2(3c)=2b+6c](https://tex.z-dn.net/?f=2%28b%29%2B2%283c%29%3D2b%2B6c)
![2b+6c= 2b+6c](https://tex.z-dn.net/?f=2b%2B6c%3D%202b%2B6c)
therefore
Choice C is equivalent to the given expression